Long-term effects of chemotherapy in children with cancer - Lenny Gannika; Mulyadi Mulyadi; Gresty Natalia Maria Masi (Malahayati International Journal of Nursing and Health Science, 2023)
Background: Cancer is a non-communicable disease that poses a health problem worldwide, including in Indonesia, affecting not only adults but also children. The most commonly used cancer therapy is chemotherapy, yet it still has effects that can impact children both physically and psychologicallyPurpose: To identify the frequently experienced impacts of chemotherapy on children based on assessments conducted by parents at the "Estella" Children's Cancer Center, Prof. Dr. Kandou Hospital.Method: This research utilized a quantitative descriptive method. The sampling technique employed was consecutive sampling, involving a total of 41 respondents. The study was conducted during the period of July-August 2023. Data was gathered using the Chemotherapy-Symptom Assessment Scale (C-SAS), comprising 23 questions. Data analysis utilized frequency distribution.Results: The research findings indicated that 80.5% of children experience alopecia (hair loss), and 80% of children considered nausea and vomiting as the most disruptive physical effects of chemotherapy, with mood swings being identified as the most disruptive psychological effect.Conclusion: Parents need to pay attention to the effects of chemotherapy to enhance the quality of life for their children during their chemotherapy treatments. It is hoped that the results of this research can be utilized by parents to manage the effects of chemotherapy on pediatric cancer patients.